1996
DOI: 10.1093/intimm/8.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte macrophage colony stimulating factor induces FcεRII/CD23 expression on normal human polymorphonuclear neutrophils

Abstract: Three major molecules have been recognized as IgE-binding structures on hematopoietic cells: the heterotrimeric high-affinity receptor for IgE (Fc epsilon RI), the low-affinity receptor for IgE (Fc epsilon RII/CD23) and the Mac-2/IgE-binding protein (epsilon BP). The latter has been shown to be expressed on polymorphonuclear neutrophils (PMN), where it regulates IgE-dependent activation. Experiments were undertaken to determine whether the IgE-binding capacity of PMN is mediated exclusively by this molecule. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…The presence of the three forms of IgE-receptor/IgE-binding molecule (FcRI, FcRII/CD23, and BP/mac-2/galectin-3) has previously been reported in neutrophils (32)(33)(34)(35)(36). The next experiments were performed to identify the types of IgE receptor/IgEbinding molecule involved in IgE-dependent ECP release.…”
Section: Figurementioning
confidence: 80%
See 1 more Smart Citation
“…The presence of the three forms of IgE-receptor/IgE-binding molecule (FcRI, FcRII/CD23, and BP/mac-2/galectin-3) has previously been reported in neutrophils (32)(33)(34)(35)(36). The next experiments were performed to identify the types of IgE receptor/IgEbinding molecule involved in IgE-dependent ECP release.…”
Section: Figurementioning
confidence: 80%
“…Several studies have reported evidence linking the presence of neutrophils with airway damage and dysfunction (29 -31). IgE can bind on neutrophils at the high-affinity receptor for IgE (FcRI) (32), the lowaffinity receptor for IgE (FcRII/CD23) (33,34), and galectin-3 (35,36). We have previously shown that specific Ags were able to activate functional responses by neutrophils from allergic patients sensitized to Ags of the same type as those which produce clinical allergic symptoms.…”
Section: E Osinophil Cationic Protein (Ecp)mentioning
confidence: 99%
“…To date, three types of IgE receptor have been identified in neutrophils: galactin 3 (Mac-2/BP) (17), the low-affinity receptor (FcRII/CD23) (18), and the high-affinity FcRI (11). FcRI binds IgE with a much higher affinity (Ͼ1000-fold) than FcRII (19) and in AA neutrophils IgE primarily binds FcRI (11).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated the presence of the three forms of IgE receptor on human neutrophils [16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26]. We have previously shown that specific allergens were able to activate functional responses by neutrophils from allergic patients sensitized to allergens of the same type as those which produce clinical allergic symptoms [27].…”
Section: Discussionmentioning
confidence: 99%
“…Elastase is a proteolytic enzyme contained in the azurophilic granules of neutrophils, and has been reported to cause epithelial damage [10], vascular hyperpermeability [11], mucus hypersecretion [12], mucus gland metaplasia [13], reduction in mucociliary clearance [14], bronchoconstriction and airway hyperresponsiveness [15]. Previous studies have demonstrated the presence of the three forms of IgE receptor – the heterotrimeric high-affinity receptor for IgE (FcεRI) [16, 17, 18, 19], the low-affinity receptor for IgE (FcεRII/CD23) [20, 21, 22]and galectin-3 [23, 24, 25, 26]– on human neutrophils. We have previously shown that specific allergens were able to activate functional responses by neutrophils from allergic patients sensitized to allergens of the same type that produced clinical allergic symptoms [27].…”
Section: Introductionmentioning
confidence: 99%